Corticosteroids as Adjunctive Therapy in the Treatment of Influenza: An Updated Cochrane Systematic Review and Meta-analysis. Issue 2 (February 2020) - Lansbury, Louise E.; Rodrigo, Chamira; Leonardi-Bee, Jo; Nguyen-Van-Tam, Jonathan; Shen Lim, Wei
Abstract : Objectives: Corticosteroids may be beneficial in sepsis, but uncertainty remains over their effects in severe influenza. This systematic review updates the current evidence regarding corticosteroids in the treatment of influenza and examines the effect of dose on outcome. Data Sources: Electronic databases (MEDLINE, EMBASE, CINAHL, LILACS, CENTRAL, and Web of Science) and trial registries were searched to October 2018 for randomized controlled trials, quasi-experimental designs, and observational cohort studies reporting corticosteroid versus no corticosteroid treatment in individuals with influenza. Study Selection and Data Extraction: Two researchers independently assessed studies for inclusion. Risk of bias was assessed using the Cochrane Risk of Bias tool (randomized controlled trials) or Newcastle-Ottawa Scale (observational studies). Where appropriate, we estimated the effect of corticosteroids by random-effects meta-analyses using the generic inverse variance method. Meta–regression analysis was used to assess the association of corticosteroid dose and mortality. Data Synthesis: We identified 30 eligible studies, all observational apart from one randomized controlled trial. Twenty-one observational studies were included in the meta-analysis of mortality, which suggested an adverse association with corticosteroid therapy (odds ratio, 3.90; 95% CI, 2.31–6.60; 15 studies; adjusted hazard ratio, 1.49; 95% CI, 1.09–2.02; six studies). Risk of bias assessment was consistent with potential confounding by indication. Pooled analysis of seven studies showed increased odds of hospital-acquired infection in people treated with corticosteroids (unadjusted odds ratio, 2.74; 95% CI, 1.51–4.95). Meta-regression of the effect of dose on mortality did not reveal an association, but reported doses of corticosteroids in included studies were high (mostly > 40 mg methylprednisolone [or equivalent] per day). Conclusions: Corticosteroid treatment in influenza is associated with increased mortality and hospital-acquired infection, but the evidence relates mainly to high corticosteroid doses and is of low quality with potential confounding by indication a major concern. Abstract : Supplemental Digital Content is available in the text.